Exploring the capacity of microorganism treatment for fermentation and glycosidic aroma bioconversion from rose oil distillation wastewater - Mohammad Karami; Mohsen Bagheri; Alireza Abbasi-Baharanchi; Kamahladin Haghbeen; Abdolrahim Nouri; Ali Asghar Karkhane; Mansour Ghorbanpour; Mohsen Farhadpour (Chemical and Biological Technologies in Agriculture)
Abstract Background One of the main concerns for ecological sustainability is finding ways to convert byproducts from medicinal aroma plants into high-value ingredients. The Damask rose (Rosa damascena Mill.) is a valuable species of aromatic rose that is grown in specific floriculture regions of Iran for the extraction of essential oils or preparation of rose water. The rose is widely used in cosmetics, flavor or fragrance formulations, and pharmaceutical products worldwide. The process of water-steam distillation is commonly used to extract rose oil, with an extraction efficiency of ~ 0.03–0.05% for active components. However, a significant amount of waste is generated during this process, with a large portion of the distillate being composed of water. This waste is known as rose oil hydrodistillation wastewater (RODW) and is considered a biocontaminant. It poses major ecological difficulties when disposed of in surface water and public drainage systems, due to the high concentration of complex degradable chemical compounds, such as polyphenols. Results This study highlights the potential of using three different types of microorganisms, namely Lactobacillus acidophilus, Pichia pastoris, and Saccharomyces cerevisiae for the conversion of glycosidically conjugated forms of nonvolatile aroma precursors into valuable aroma compounds. Gas chromatography-mass spectrometry (GC–MS) analysis demonstrated that all three microorganisms could affect the concentration of volatile components. However, when the sample was treated with S. cerevisiae for 120 h, the highest levels of recovery were observed for phenyl ethyl alcohol and eucalyptol, which were 2.5 and 80 times greater than those of the untreated sample, respectively. Moreover, the levels of α-pinene and anethole were also increased to ~ 9.7 and 11.7 times after 48 h of treatment, respectively. Additionally, the fermentation process increased in the total phenolic and flavonoid contents. Conclusion Using different microbial biocatalysts to recover natural bioactive aroma compounds is an attractive and scalable bioconversion methodology for producing value-added chemical derivatives from the waste of medicinal plants. Graphical abstract